Direito à vida do nascituro - Teixeira Junior, Flávio Luiz (2009)
This work aims to present that, in the brazilian law, the unborn is human person since the conception, owning rights originated of his personality, althought the most important is the fundamental right to life. The subject matter involving this right to life originates of the respect to dignity of the human person value, which runs the principle of human life, inserted in the Federal Constitution, but also incorporated by the international conventions that the Brazil is signatary, and that influences all the brazilian juridic ordenament. As the right is coherence and uniformity, it presents that the protection of the right to life of the unborn happens as much by the civilistic optic like with the right to support recognized by doctrine and jurisprudence, and with the heatlhy development of the pregnancy, product of the total protection doctrine , as by the penal optic, with the tipification of the offense of the abortion. This protection happens even though the seed of relativization of this right to life, like in the judgment of the constitutionality of using human embryo as a source of steam cell, by divergent interpretations of legal texts, or by the appeal for the legalization of the eugenic abortion